PERBANDINGAN VOLATILITAS EWMA, GARCH DAN MONTE CARLO TERHADAP NILAI TUKAR MATA UANG ASING BANK Bjb - Safrin Marulitua, AK., MBA., CPA., CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This research addresses the comparison of accuracy volatility models especially Exponentiall Weighted Moving Average (EWMA), Generalized Autoregressive Conditional Heteroscedastic (GARCH) with its classification and Monte Carlo Simulation (MCS) for measuring market risk in order to calculate VaR of portofolio to exchange rate of AUD/IDR, EUR/IDR and USD/IDR of Bank Bjb. Testing in the validity of the model using Kupiec mixed backtest shows that GARCH volatility model and its classification with confidence level of 95% proved that three foreign currency exchange rate AUD, EUR and USD has valid and accurate model, while EWMA valid for AUD and EUR currencies and MCS valid for USD currency. Results of the portfolio market risk VaR estimation using filtered historical simulation method as amount of Rp797.083.763, gives information reserve capital or minimum capital charge to be provided by Bank BJB, in addition must also take into account the credit risk and operational risk.